TINGKAT KEPUASAN PASIEN RAWAT JALAN TERHADAP PELAYANAN KEFARMASIAN DI INSTALASI FARMASI RUMAH SAKIT MARINIR CILANDAK JAKARTA - Jenny Pontoan; Okpri Meila; Yuli Asnanik; Muhammad Azhar Muharam (Jurnal Ilmiah Manuntung, 2020)
Measuring the quality dimensions of health service is essential and should be done along with patient satisfaction surveys. The level of patient satisfaction with hospital health services may use the five-dimensional Service Quality (ServQual) method, that is, reliability, responsiveness, assurance, concern and tangible form. The study was conducted to determine the level of outpatient satisfaction with the quality of services provided by The Cilandak Marinir Hospital Pharmacy Installation. The research design is Observational by survey methods, conducted on JKN outpatients, with a total sample of 106 respondents. Inclusion criteria; patients who redeem a prescription at a hospital pharmacy installation at least 2 times; patients who are willing to fill out the questionnaire, sign the questionnaire, and approve the informed consent; patients aged ≥ 15 years. Exclusion criteria are patients who are hospital employees; HIV / AIDS patients. This study was also complemented with data collection permits from the hospital and ethical approval from the ethics research committee of the Universitas Pembangunan Veteran Jakarta. The instrument used is in the form of a questionnaire to measure patient satisfaction about pharmacy services at the pharmacy. The results of the validity test of 0.383-0.950 (components of expectations) and 0.362-0.928 (components of performance) are declared valid. The reliability test results are 0.954-0.961 (expectation component) and 0.951-0.960 (performance component); these results indicate that the questionnaire can be used because all questions are reliable (> 0.60 Cronbach Alpha scores). Data analysis uses the Service Quality method (Service Quality score = Performance - Expectation). A positive score indicates that customer expectations are met so that services on specific dimensions can be perceived as high quality and vice versa. Ideally, the value of the gap between expectations and perceptions is zero. ServQual analysis results based on the gap showed that the most significant value of the gap in the dimensions of reliability -0.18, responsiveness (responsiveness) -0.12, awareness (empathy) -0.08, assurance -0, 07, and tangible form (tangible) -0.03. Based on these results, It can be concluded that pharmaceutical services still need improvement because they still have a negative gap value for the five dimensions.